1
$\begingroup$

Could someone explain me this equation? $$\sum_{n=1}^\infty \frac{1}{2^{n}\ n} =\log (2)$$ I am to calculate the sum of the expression on the left side. I was looking for mathematical formulas, any templates, but nothing was found. Have you got any idea?

$\endgroup$
  • 2
    $\begingroup$ Hint: think about how you might evaluate $\sum_{n=1}^{\infty} \frac{1}{n2^n} x^n = \sum_{n=1}^{\infty} \frac{1}{n} \left(\frac{x}{2}\right)^n$ $\endgroup$ – Antonio Vargas Jul 26 '14 at 20:38
  • 1
    $\begingroup$ Consider the Taylor series for $\log(1-x)$. $\endgroup$ – lemon Jul 26 '14 at 20:42
  • $\begingroup$ Another method: Integrate both sides of sum of x^n/2^n = x/2/[1-x/2], manipulate terms a little and then substitute 1 for x. $\endgroup$ – berkeleychocolate Jul 26 '14 at 20:44
  • $\begingroup$ @AntonioVargas do you have another hint? I'm interested in how you proceed on from there $\endgroup$ – DanZimm Jul 26 '14 at 20:52
  • 1
    $\begingroup$ @DanZimm, See MathFacts' answer for more :) $\endgroup$ – Antonio Vargas Jul 26 '14 at 21:02
8
$\begingroup$

Since: $$ \frac{x^{n+1}}{n+1}=\int_{0}^{x} y^n\,dy,$$ you have: $$ S = \sum_{n=1}^{+\infty}\int_{0}^{1/2} y^{n-1}\,dy = \int_{0}^{1/2}\sum_{n=0}^{+\infty}y^n\,dy = \int_{0}^{1/2}\frac{dy}{1-y}=\left.-\log(1-y)\right|_{0}^{1/2}=\log 2.$$

$\endgroup$
  • 1
    $\begingroup$ Thank you very much, it is very helpful ;) $\endgroup$ – Thomenson Jul 26 '14 at 20:46
  • 1
    $\begingroup$ This is a beautiful presentation of this! $\endgroup$ – mathematician Jul 26 '14 at 20:49
  • $\begingroup$ @oliveeuler no, we have $\sum_{n=1}^\infty \frac{1}{n2^n} = \sum_{n = 1}^\infty \int_0^{1 / 2} y^{n-1} dy$ $\endgroup$ – DanZimm Jul 26 '14 at 20:51
  • $\begingroup$ @DanZimm I'd missed that the $y^{n}$ changed to $y^{n-1}$; my mistake. $\endgroup$ – Jam Jul 26 '14 at 20:53
3
$\begingroup$

Let $$ f(x) = \sum_{n=1}^{\infty}\frac{x^n}{n2^n} \quad \Rightarrow \quad f^{\prime}(x) = \sum_{n=1}^{\infty}\frac{x^{n-1}}{2^n} = \frac{1}{x}\sum_{n=1}^{\infty}(x/2)^n = \frac{x/2}{x(1 - x/2)} = \frac{1}{2 - x} $$ Thus, $$ f(x) = -\ln (2 - x) + C $$ For $x = 0$, $C = \ln 2$ and $f(x) = \ln \frac{2}{2 - x}$.

For $x = 1$, we have $$ \sum_{n=1}^{\infty}\frac{1}{n2^n} = f(1) = \ln 2 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.